Three essays on property and liability insurance company investment - Lou, Pingyi (Nanyang Technological University, 2018)
My thesis discusses the investment made by Property and Liability (or Property and Casualty) insurance companies. We also study the spillover effect of the investment made by these insurance companies as well. In Chapter One, we introduce the background and preview the results. In Chapter Two, we discuss how the regulation will affect insurance investment behavior. We explore the impact of capital adequacy requirements on financial institutions’ risk-taking behavior from a new perspective. Specifically, we show that one important feature of the risk-based capital (RBC) system, a built-in diversification benefit in aggregating risk categories, induces moral hazard. We find that insurers that face lower RBC costs of fixed-income (FI) investment purchase more risky FI securities. Using Hurricane Katrina and Hurricane Sandy as exogenous shocks to RBC cost, we find that the insurers that suffered more in the two disasters took more risk in their FI investments and that their overall risk increased. These results provide an important regulatory implication for minimum capital calculation in capital regulation regimes. In Chapter Three, we discuss how the organizational forms will affect Property and Casualty (P&C) insurance companies’ investment in underwriting business, from the perspective of internal asset allocation. We study how the return of internal capital markets (ICMs) and the risk of ICMs differ across three alternative organizational forms: publicly-held stock insurers, privately-held stock insurers and mutual insurers. Because of the different combination of owner, manager and customer functions, these three organizational forms are subjected to different aspects and extents of agency problems, which leads to a variation in the performance of ICMs. In terms of return, we find that the sensitivity of investment increase in highly profitable business lines to ICM subsidy is significantly positive for private insurers, but is insignificant for mutual and public insurers. In terms of risk, we find that the sensitivity of investment increase in highly profitable and highly risky business lines to ICM subsidy is significantly positive for public insurers. Finally, we shed light on the association between organizational forms and shadow insurance, one specific ICM transaction associated with increasing firm-level risk. We find that the underwriting ROA volatility is more sensitive to shadow ICM subsidy than to regular ICM subsidy for public insurers. In Chapter Four, we study the spillover effect of P&C insurance companies’ investment behavior. We examine whether the financial health of municipal bond investors can affect the municipal borrowing cost, i.e., the municipal bond yield, especially focusing on the liquidity component. Using the U.S. property and casualty insurance companies as the research setting, we find that the deterioration of the financial health of bond investors raises the liquidity spread of municipal bonds, and this relationship was even stronger during the subprime mortgage crisis. Using Hurricane Sandy as an exogenous shock to the financial health of insurers, we find that the municipal bonds held by insurers suffered loss by the hurricane experience larger increase in liquidity yields in the current and following quarter of Hurricane Sandy. In Chapter Five, I make a conclusion of my thesis.